PENGARUH METODE TAKTIS PASSING STATIS TERHADAP KETERAMPILAN PASSING FUTSAL DI SMP NEGERI 2 CIASEM - Purnama, Agung; Ma’mun, Saepul; Syafei, Muhammad Mury (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Passing is an important basic technique in the game of futsal, the purpose of this technique is to feed or divide the ball to teammates, when passing someone must pay attention to the position of the friend who will be baited and the opponent who is guarding it so that the ball can arrive and not be seized by opponent, usually passing is done at close range to build an attack. This research method is a pre experimental design, with a One-Group Pretest-Posttest Design with a population of extracurricular students at SMP Negeri 2 Ciasem, and the sample taken is 20 people, analysis of research data to see the effect of using simple linear regression. The results of this study obtained the lowest pretest score was 10 and the highest was 80 with an average of 35.0, while the lowest posttest score was 40 and the highest was 100 with an average of 73.0 Based on the results of research and discussion that has been described, it can be concluded that the level of futsal passing skills of extracurricular students at SMP Negeri 2 Ciasem by using the tactical approach of static passing increased by 38%..